2018
DOI: 10.31272/jeasd.2018.2.23
|View full text |Cite
|
Sign up to set email alerts
|

Bond Strength of Light-Weight Concrete Pull-Out Specimens Contain Steel Fibers

Abstract: Bond between reinforcing steel bar and concrete has a critical influence on the structural behavior of reinforced concrete members. The nature of the concrete makes the bond characteristics inherently variable. The variability of the bond affects some of the more practical parameters such as the embedded length, bar diameter and cover thickness, which, in turn, considerably influence the length of the reinforcing elements used in the fabrication of the composite. In this investigation, the bond strength of nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The results indicated an increase in the bond strength upon decreasing the w/c ratio and upon increasing the diameter of the bars. Further, Abbas et al [17] investigated the effect of different variables, such as bonded length, bar diameter, and concrete cover, on the bond strength of lightweight concrete (LWC) containing steel fibers and porcellanitic as coarse aggregate. It was found that the bond strength of normal weight concrete was higher compared to LWC [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated an increase in the bond strength upon decreasing the w/c ratio and upon increasing the diameter of the bars. Further, Abbas et al [17] investigated the effect of different variables, such as bonded length, bar diameter, and concrete cover, on the bond strength of lightweight concrete (LWC) containing steel fibers and porcellanitic as coarse aggregate. It was found that the bond strength of normal weight concrete was higher compared to LWC [18,19].…”
Section: Introductionmentioning
confidence: 99%